Characterization of resistance genes and plasmids from sick children caused by Salmonella enterica resistance to azithromycin in Shenzhen, China - Wang, Hongmei; Cheng, Hang; Huang, Baoxing; Hu, Xiumei; Chen, Yunsheng; Zheng, Lei; Yang, Liang; Deng, Jikui; Wang, Qian (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Samonella is 1 of 4 key global causes of diarrhoeal diseases, sometimes it can be serious, especially for yong children. Due to the extensive resistance of salmonella serotypes to conventional first-line drugs, macrolides (such as azithromycin) have been designated as the most important antibiotics for the treatment of salmonella. Antimicrobial resistance is a major public health problem in the world, and the mechanism of azithromycin resistance is rarely studied. Methods This study determined the azithromycin resistance and plasmids of Salmonella enterica isolates from children attending the Shenzhen Children’s Hospital. The susceptibility of ampicillin (AMP), ciprofloxacin (CIP), ceftriaxone (CRO), sulfamethoxazole (SMZ), chloramphenicol (CL), and azithromycin (AZM) were detected and the genes and plasmids from azithromycin-resistant Salmonella were detected by Illumina hi-seq and Nanopore MinIone whole genome sequencing (WGS) using a map-based method, and the genomic background of these factors was evaluated using various bioinformatics tools. Results In total, 15 strains of nontyphoid Salmonella strains that were isolated (including S. typhimurium, S.London, S. Goldcoast, and S.Stanley) demonstrated resistance to azithromycin (minimum inhibitory concentration,MIC from 32 to >256 µg/mL), and the resistance rate was 3.08% (15/487). The sensitivity test to other antibiotics demonstrated 100% resistance to AMP, and the resistance to SMZ and CL was 86.7% and 80.0%, respectively. Through WGS analysis, all isolates were positive for a plasmid-encoded mphA gene. Plasmid incompatibility typing identified five IncFIB(K), five IncHI2/HI2A/Q1, two IncC, one IncHI2/HI2A/N, one IncR, one IncFII and one IncHI2/HI2A plasmids. Sequence analyses of plasmids revealed extensive homology to various plasmids or transposons in regions involved in plasmid replication/maintenance functions and/or in antibiotic resistance gene clusters. Conclusion mphA is the main gene involved in azithromycin, a macrolide, and resistance to Salmonella. It is usually located on plasmids and easily spreads, hence posing a great threat to the current treatment of Salmonella infection. The plasmid sequence similarities suggest that the plasmids acquired resistance genes from a variety of enterica bacteria and underscore the importance of a further understanding of horizontal gene transfer among enterica bacteria.